Programming microcontrollers in C - Van Sickle, Ted. (Eagle Rock, Calif. : LLH Technology Pub., 2001)
Ted Van Sickle spent over fifteen years at Motorola as a microcontroller specialist. He now consults and teaches classes on software design and programming for microcontroller systems. He holds a MSEE from the University of Michigan.
Introduction to C -- Advanced C topics -- What are microcontrollers? -- Small 8-bit systems -- Programming large 8-bit systems -- Large microcontrollers -- Advanced topics in programming embedded systems (M68HC12) -- MCORE, a RISC machine.
Includes index.
Keywords: Programmable controllers; C (Computer program language) -- Study and teaching; Electronic books